Assessment of Bacterial Communities in Thirteen Species of Laboratory-Cultured Domestic Mites (Acari: Acaridida) - Hubert, Jan; Kopecky, Jan; Sagova-Mareckova, Marketa; Nesvorna, Marta; Zurek, Ludek; Erban, Tomas (Journal of economic entomology, 2016)
House dust mites (HDMs) and stored-product mites (SPMs) of various species inhabit human homes and stored agricultural products. These mites are carriers and hosts of microorganisms that enable their survival. The bacteriome from 13 species of SPMs and HDMs was analyzed and compared by 454 pyrosequencing of partial 16S rRNA gene amplicons. Altogether 128,052 sequences were obtained and assigned to 71 operational taxonomic units (OTUs) at the 97% identity level. The number of sequences in the OTUs between species of mites ranged from 6 to 31 in the individual mite species. We did not find any significant effect of diet or evolutionary origin of mites or their interaction on the composition of the mite bacteriome. In mite species with low bacterial diversity, the bacterial communities were dominated by potential symbiotic or parasitic bacteria, i.e., Cardinium in Dermatophagoides farinae (Hughes, 1961) and Aeroglyphus robustus (Banks 1906) and the enteric bacteria Erwinia in Blomia tropicalis Van Bronswijk, de Cock & Oshima, 1974 and Xenorhabdus in Tyroborus lini (Oudemans, 1924). Among the bacterial species identified, Staphylococcus, Bacillus, Kocuria, Brevibacterium, Corynebacterium, and Brachybacterium likely serve as food sources for the mites. The domestic acaridid mites carried high numbers of various bacteria that are potential threats to human health. These results contribute to the general understanding of the ecology of mite adaptation to human-made habitats.
Keywords: mikrobiota; symbiont; Sequence Analysis, DNA; bacteria; parasite; bakteriální RNA; RNA ribozomální 16S; sekvenční analýza DNA; feeding; Bacteria; Animals; Mites; allergen; RNA, Bacterial; Microbiota; zvířata; roztoči; RNA, Ribosomal, 16S